2012
DOI: 10.4283/jmag.2012.17.1.046
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-Based Design Optimization of a Superconducting Magnetic Energy Storage System (SMES) Utilizing Reliability Index Approach

Abstract: A reliability-based optimization method for electromagnetic design is presented to take uncertainties of design parameters into account. The method can provide an optimal design satisfying a specified confidence level in the presence of uncertain parameters. To achieve the goal, the reliability index approach based on the firstorder reliability method is adopted to deal with probabilistic constraint functions and a double-loop optimization algorithm is implemented to obtain an optimum. The proposed method is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…2 [10,11]. For solving (5), the Hasofer-Lind and Rackwitz-Fiessler (HL-RF) method is employed here because of its simplicity and efficiency [11][12][13].…”
Section: Reliability Analysis Using Riamentioning
confidence: 99%
See 2 more Smart Citations
“…2 [10,11]. For solving (5), the Hasofer-Lind and Rackwitz-Fiessler (HL-RF) method is employed here because of its simplicity and efficiency [11][12][13].…”
Section: Reliability Analysis Using Riamentioning
confidence: 99%
“…3. Such a double-loop optimisation structure inherently demands very high computational cost because the sub-optimisation problem of (5) has to be solved for each probabilistic constraint function given at every design point [11][12][13][14][15].…”
Section: Implementation Of Rbdo Based On Riamentioning
confidence: 99%
See 1 more Smart Citation
“…So the efficiency is very low. There are mainly two strategies to improve the efficiency of the RBMDO: (1) improve the reliability analysis efficiency, such as reliability index approach (RIA) 41 and PMA 42 and (2) change the architecture of RBMDO.…”
Section: Rbmdomentioning
confidence: 99%
“…To implement such reliability analysis, an additional optimization problem, of which the goal is to find the most probable failure point (MPP) in the normal design space, has to be solved. Consequently, it is revealed that RBDO has a doubleloop optimization structure [6]- [8]: to find an optimum of the objective function as a main loop, and to satisfy the given probabilities of constraints as a sub-loop. In spite of the benefit of RBDO, such a double-loop strategy inevitably demands an extremely high computational cost.…”
Section: Introductionmentioning
confidence: 99%